Implementasi Peraturan Daerah Kabupaten Badung Nomor 7 Tahun 2012 tentang Pengaturan Pasar Tradisional di Kabupaten Badung - I Putu Gede Murditayasa; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2021)
Traditional markets are meeting place for traders and buyers, where trade is carried out by negotiation and bargaining. However, along with the times there has been a decline in the performance of traditional markets due to the existence of modern markets and the weak competitiveness of entrepreneurs conducting activities in traditional markets. This study aims to explain the procedures for implementing the revitalization of the Regional Regulation of Badung Regency Number 7 of 2012 concerning the regulation of traditional markets in Badung Regency and to analyze the inhibiting factors for the implementation of the Regional Regulation. This study uses an empirical legal research type using a statutory approach. The data used are primary and secondary data. The results show that the implementation of the revitalization of traditional market development in the Badung area is one of the moves by the government in charge of the regions in terms of reviving and re-developing markets which previously experienced a decline due to competition with growing modern markets, for this reason, the promulgation of regional regulation number 7 2012 concerning the arrangement and fostering of traditional markets, shopping centers and modern shops to make the existence of traditional markets better and their development, the second obstacle to the implementation of regional regulation number 7 of 2012 concerning the arrangement and development of traditional markets, shopping centers and modern shops lies in the enforcement factor, regulations, funding factors, management factors and community factors.